JURIDICAL ANALYSIS OF THE ROLE AND RESPONSIBILITIES OF IMMIGRATION CONTROL ON THE USE OF PASSPORTS FOR INDONESIAN MIGRANT WORKERS (PMI) IN A NONPROCEDURAL BASIS FROM THE PERSPECTIVE OF LEGAL CERTAINTY (RESEARCH STUDY AT THE CLASS I IMMIGRATION OFFICE SPE - Ricky Rahmawan; Fadlan; Erniyanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The departure of Indonesian Migrant Workers (PMI) was under the pretext of protecting Indonesian citizens abroad. This is certainly not in line with the constitution, so there needs to be improvements to the procedures for protecting Indonesian Migrant Workers (PMI). The domino effect is that these non-procedural Indonesian Migrant Workers (PMI) will continue to try to leave "like the theory of a squeezed balloon" or illegally via rat routes which will be very dangerous for these Indonesian Migrant Workers (PMI). Based on the research results, it was found that the factors causing the problem were due to the absence of norms (no governing law), there were no clear parameters between Indonesian citizens who were just passing through and Indonesian Migrant Workers (PMI). Then, during the passport interview process, Immigration officers also did not can predict whether a passport that is valid for 10 years will be used for tourism only or for work purposes. Especially in Batam and other border areas, officers will find it difficult to determine which are Illegal Indonesian Migrant Workers (PMI) and which are seasonal workers. For this reason, it is hoped that the inspection system implemented by the Immigration Office will begin with the completeness and authenticity of the documents required in the passport application process, namely verifying the authenticity of the data provided whether it is as requested or not, so that the role of immigration in combating transnational crime is very important. large and strategic, this is related to its duties and functions as a gatekeeper to Indonesian territory, regarding the flow of traffic entering Indonesia, immigration implements a selective policy (selective policy).